2000
DOI: 10.1007/s100720070119
|View full text |Cite
|
Sign up to set email alerts
|

Deafness: an unusual onset of genetic Creutzfeldt-Jakob disease

Abstract: We describe a case of genetic Creutzfeldt-Jakob disease (CJD) with deafness at the onset. We report clinical features, 14-3-3 protein positivity, electroencephalography and brain stem auditory evoked potential abnormalities, and high signal on magnetic resonance imaging in basal ganglia and temporal cortex. Similarities with CJD Heidenhain variant are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This heterogeneity mirrors other reports of sCJD. A wide spectrum of focal presentations have been reported that include aphasia, 1-3 9-11 ataxia, 3 15 16 visual impairments, 1-5 12 cortical deafness, [17][18][19] depression, 20 and obsessive-compulsive disorder. 21 In other patients the presentation is relatively nonspecific and may consist of lethargy and difficulty in concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity mirrors other reports of sCJD. A wide spectrum of focal presentations have been reported that include aphasia, 1-3 9-11 ataxia, 3 15 16 visual impairments, 1-5 12 cortical deafness, [17][18][19] depression, 20 and obsessive-compulsive disorder. 21 In other patients the presentation is relatively nonspecific and may consist of lethargy and difficulty in concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Only two cases of CJD with deafness at onset have been published: one sporadic, associated with symptoms suggestive of polyneuropathy,2 and the other familial, with the E200K mutation and typical features 3. Other cases have been reported as presenting with auditory agnosia or with cortical deafness, and early involvement of the acoustic pathway has already been detected through demonstration of progressive BAEP deterioration in patients with CJD who did not present deafness in the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…She later developed signs of polyneuropathy and mental deterioration, left homonynous hemianopsia and decreased vibratory and pinprick sensation. The second case was that of a 46-year-old Italian woman with the E200K mutation, who had rapidly worsening hearing loss 3. At 3 weeks after presentation she developed an unstable gait, and her condition rapidly progressed to bilateral deafness, ataxia, myoclonus, pyramidal and extrapyramidal dysfunction, and mental deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…85,86 Deafness can occur in mitochondrial disease, 90 MohrTranebjaerg syndrome, 101 Whipple disease, 34 HIV, 116 antiphospholipid syndrome, 99 Susac syndrome, 108 Fabry disease, 110 familial Danish dementia, 91 superficial siderosis, 80 variants of hereditary sensory and autonomic neuropathy type 1 with deafness and dementia, 118 and genetic prion disease. 127 Auditory agnosia with pure word deafness has been reported to occur as a result of vascular or space occupying lesions affecting the auditory cortex or subcortical structures such the medial geniculate body or the posterior limb of the internal capsule, 128,129 or rarely in the context of FTLD. 130 The presence of REM sleep behavior disorder, in which patients seem to be acting out their dreams, may be an indicator of early DLB or PDD.…”
Section: Other Neurologic Symptoms/signs Presentmentioning
confidence: 99%